PENGARUH BUDAYA KERJA DAN KOMITMEN TERHADAP KINERJA PERAWAT DI RSUP HAJI ADAM MALIK MEDAN - LAMMINAR HUTABARAT (LP2MTBM MAKARIOZ, 2020)
Optimal employee performance is the most important requirement in achieving the company's Goal. The company's achievement is derived from the company's efforts to manage its human resources in order to improve its work. The company's human resource management is reflected in the employee's performance and results from achieving the company's objectives. The effective and efficient implementation of employee performance systems will greatly influence the achievement of employee performance impacting the achievement of the company's performance. One company that needs employees with a high level of performance is a company that is engaged in the health of the hospital. This research aims to know and analyse the influence of work culture and commitment to the performance of employees in RSUP H. Adam Malik Medan. Respondents in this study were nurses in RSUP H. Adam Malik Medan Marelan amounted to 89 people. The data collection techniques in this study use interviews, questionnaires, observations, literature studies, and documentation studies. The data analysis method used is multiple linear regression, to know the relationship between the variables freely to the bound variables.Based on multiple linear regression test results, indicating that the working culture with a value of 0681 units is the variable having the most dominant relationship to the employee performance variable, while the commitment has a smaller value with the value of 0326 units. Based on partial and simultaneous hypothesis testing, it shows that work culture and commitment have a positive and significant influence on employee performance. The results of the coefficient of determination test using R-Square obtained the result that the contribution of working culture and commitment in influencing employee performance is 62.5%.